The occurrence of bovine leucosis in the state of Pernambuco, Brazil - Cavalcante, Maria Ignês; Barreto, Silvio Camerino Paes; Costa Filho, Guilherme Antonio da (Pesquisa Agropecuaria Brasileira, 2014)
The occurrence of bovine leucosis in zebu steers of the State of Pernambuco, Brazil, is described. Diagnosis was based on clinical, haematological and histopathological examinations.